Marine biomaterials : characterization, isolation, and applications - Kim, Se-Kwon (Taylor & Francis, 2013)
Oceans are an abundant source of diverse biomaterials with potential for an array of uses. Marine Biomaterials: Characterization, Isolation and Applications brings together the wide range of research in this important area, including the latest developments and applications, from preliminary research to clinical trials. The book is divided into four parts, with chapters written by experts from around the world. Biomaterials described come from a variety of marine sources, such as fish, algae, microorganisms, crustaceans, and mollusks. Part I covers the isolation and characterization of marine.